(untitled) (Eurasian Journal of Philology Science and Education, 2016)
Kazakhstani foreign language education policy as the policy of the whole world educational community has shifted a focus from simple communicative competence which was a goal of foreign language education for over three decades in FLT (1970-1990) to intercultural communicative competence, as a simple acquisition of purely functional use of language didn’t satisfy the needs of learners as well as teachers in the conditions of necessity of constant interactions on the international level. Therefore the aim of this article is to reveal the ways of developing foreign language learners’ intercultural communicative competence in the conditions of Kazakhstani educational system on the base of defining the notion and structure of intercultural communicative competence, determining the main factors of developing this quality and consequently to work out some scientific and methodological recommendations.